Respuesta :

The correct answer is: Option 3: [tex](hofog)(x)=\frac{x-14}{x+4}[/tex]

Step-by-step explanation:

Given

[tex]f(x)=\frac{x-6}{x}\\g(x)=x+4\\h(x)=3x-2[/tex]

We have to find

[tex](hofog)(x)[/tex]

This will be equal to:

[tex]h(f(g(x)))[/tex]

So we have to find the composition of (fog)(x) first

[tex](fog)(x) = f(g(x))\\=\frac{x+4-6}{x+4}\\=\frac{x-2}{x+4}[/tex]

Now,

[tex](hofog)(x)=h(f(g(x)))\\=3(\frac{x-2}{x+4})-2\\=\frac{3x-6}{x+4}-2\\=\frac{3x-6-2(x+4)}{x+4}\\=\frac{3x-6-2x-8}{x+4}\\=\frac{x-14}{x+4}[/tex]

The correct answer is: Option 3: [tex](hofog)(x)=\frac{x-14}{x+4}[/tex]

Keywords: Composition, Functions

Learn more about function composition at:

  • brainly.com/question/10015690
  • brainly.com/question/10048445

#LearnwithBrainly